Les relations économiques sino-américaines pendant les années Bush (2001-2008) : vers une stratégie de « dissuasion économique » ? - Juliette Bourdin (Revue LISA)
During the presidency of George W. Bush, the main characteristic of US-China economic relations was an increasing interdependency in the field of trade as well as over financial issues. If trade imbalance and intellectual property rights were already matters for debate during the presidency of Bill Clinton, the issues of the value of the renminbi and of Chinese holdings of US Treasury bonds emerged during the Bush years. While the Bush administration had initially advocated a strategy of “congagement” (containment/ engagement) and had defined China as a “strategic competitor”, not only did 9/11 change Washington’s immediate priorities, but, with the US-China economic interdependency, the only realistic strategy between Washington and Beijing seemed to consist in “economic deterrence.”